Presentation of a large recurrente traumatic bone cyst; clinical case report - Salazar Casco, José (2022)
The Traumatic Bone Cyst is an intraosseous cavity that appears in the jaw of young patients. One of the most accepted theories is about bleeding inside the bone due to trauma, instead of the correct formation of the clot, the liquefactive necrotic clot is reabsorbed in another way, forming the cyst. The first objective of this clinical case is to return the functionality and correct health of the patient. The second objective is linked to the presentation of a specific clinical case, which will allow us to illustrate the treatment of the Traumatic Bone Cyst of a 16-year-old male patient, who attended an orthodontic consultation, being referred to an interconsultation with the surgery area. maxillofacial, due to discomfort in the lower right quadrant when chewing. As a complementary examination, the computerized axial tomography CT scan shows a radiolucent shadow compatible with a "bone cyst" with well-defined edges at the apical level of tooth number 45. The patient underwent biopsy of the lesion as treatment, performing a vestibular approach with lifting of the mucoperiosteal flap, window osteotomy. Its management and review of the literature is carried out.